Information Users and Usability in the Digital Age. - Chowdhury, G. G. (Facet Publishing, 2013)
Gives an overview of the necessary issues relating to information users and the usability of information services in the digital world, including user-centred design, and the characteristics and behaviour of information users. This book helps readers understand why information users and the usability of information services are important.